2013
DOI: 10.1016/j.phrs.2012.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in endocannabinoid tone following chemotherapy-induced peripheral neuropathy: Effects of endocannabinoid deactivation inhibitors targeting fatty-acid amide hydrolase and monoacylglycerol lipase in comparison to reference analgesics following cisplatin treatment

Abstract: SUMMARY Cisplatin, a platinum-derived chemotherapeutic agent, produces mechanical and cold allodynia reminiscent of chemotherapy-induced neuropathy in humans. The endocannabinoid system represents a novel target for analgesic drug development. The endocannabinoid consists of endocannabinoids (e.g. anandamide (AEA) and 2-arachidonoylglycerol (2-AG)), cannabinoid receptors (e.g. CB1 and CB2) and the enzymes controlling endocannabinoid synthesis and degradation. AEA is hydrolyzed by fatty-acid amide hydrolase (FA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
172
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(189 citation statements)
references
References 96 publications
17
172
0
Order By: Relevance
“…These agents are produced and degraded through distinct enzymemediated routes (for review, see Guindon and Hohmann, 2009). Anandamide is formed by cleavage of a membrane phospholipid in which the amine group of phosphatidylethanolamine is covalently linked to arachidonic acid.…”
Section: Endogenous Cannabinoid Agonistsmentioning
confidence: 99%
See 2 more Smart Citations
“…These agents are produced and degraded through distinct enzymemediated routes (for review, see Guindon and Hohmann, 2009). Anandamide is formed by cleavage of a membrane phospholipid in which the amine group of phosphatidylethanolamine is covalently linked to arachidonic acid.…”
Section: Endogenous Cannabinoid Agonistsmentioning
confidence: 99%
“…Monoacylglycerol lipase (MGL) is the main serine esterase involved in 2-AG deactivation (Dinh et al, 2002;, with ␣-␤ hydrolase domain 6 (ABHD-6) participating in some cases (Marrs et al, 2010). Like anandamide, 2-AG may be also metabolized by cyclooxygenase-2 to produce oxidized proalgesic derivatives (for review, see Guindon and Hohmann, 2008). 2-AG formation can be inhibited using relatively nonselective probes that block either PLC (e.g., U73122) or DGL (e.g., tetrahydrolipstatin) (Gregg et al, 2012).…”
Section: Endogenous Cannabinoid Agonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also recent evidence that CB targets may be efficacious in treating CIN. For example, selective CB1 and CB2 receptor agonists, as well as compounds that increase endocannabinoid tone, attenuate tactile allodynia in rodent models of CIN [12][13][14].Abstract ! Sativex, a cannabinoid extract with a 1 : 1 ratio of tetrahydocannabinol and cannabidiol, has been shown to alleviate neuropathic pain associated with chemotherapy.…”
mentioning
confidence: 99%
“…For example, Vera et al [12] demonstrated that cisplatin tactile allodynia in rats can be attenuated by administration of the CB selective and nonselective receptor agonists ACEA, JWH133, and WIN 55,212-2. Cisplatin tactile allodynia can also be attenuated through increased levels of the endocannabinoids anandamide and 2-arachidonylglycerol (2AG) via inhibition of fatty acid amide hydrolase (FAAH) and monoacylglycerol lipase (MGL), respectively [13]. While targeting the endocannabinoid system with THC and CBD can modulate CIN, there is a literature that reports THC exposure can lead to increased cancer cell proliferation and tumor metastasis by decreasing antitumor immune responses.…”
mentioning
confidence: 99%